Economic cost of a case of diarrhoea in Uvira, Democratic Republic of the Congo: A cost of illness study. - Patrick V Katana; Espoir Bwenge Malembaka; Patrick Musole Bugeme; Jaime Mufitini Saidi; Oliver Cumming; Karin Gallandat; Ian Ross (Public Library of Science (PLoS), 2024)
Background Diarrhoea is one of the leading causes of disability-adjusted life years (DALYs) among children below five years, though the proportion of the burden occurring amongst those aged over 70 is increasing. The cost of treating and managing diarrhoea can place a burden on individuals, their households, and society in general. The cost can be high but is often undocumented, and many studies focus on children or hospitalised patients only. This study aimed to estimate the economic cost per case of diarrhoea amongst individuals of any age in Uvira, Democratic Republic of the Congo. Methods The study was cross-sectional and retrospective, and based on a household survey approximately representative of the city undertaken in September 2021. Data on quantities and prices of resources were collected in the survey, as well as from interviews with staff at the Cholera Treatment Centre in the Uvira general hospital and their records on resource use and patient numbers. Direct and indirect costs were measured from the societal perspective, and generalised linear regression used to identify factors associated with higher costs. Results Of 2,820 members of the 528 households surveyed, 175 people (6.2%) were reported to have had diarrhoea in the previous seven days. The majority sought care (91%) of which most (64%) visited a pharmacy. The average economic cost of illness (COI) for an episode of diarrhoea was 33,816 Congolese Francs (CDF) (US$ 17.0) in 2021 prices. The median was CDF 14,000 (US$ 7.0). The average out of pocket COI to patients was CDF 15,579 (US$ 7.8), representing 9% of the estimated average monthly income of households. On average caregivers and patients lost 4 days per episode. A concentration index suggested a lower economic COI among poorer households (p=0.099). A regression analysis identified that being older than 5 years (p=0.001) or being water insecure (p=0.032) were associated with higher COI. Conclusion Households in Uvira experience many diarrhoeal episodes per year, and the COI is an important burden for them and society. These costs could be avoided if diarrhoea were prevented through public health interventions to reduce prevalence and care-seeking was better managed to avert this public health burden.